Length-Weight Relationship of Fishes in Some Rivers of Morang, Nepal - Shrestha, Sharada; Tamang, Ganesh; Limbu, Jash Hang; Rajbanshi, Dipak (Himalayan Journal of Science and Technology, 2023)
The length-weight relationship is a crucial aspect of fishery assessments, providing valuable biological information. The length-weight relationship is expressed by the equation W = aLb, where W represents the total weight of the fish and L denotes the standard length. The LWR equation was transformed into a linear form using logarithmic transformation: LogW = a + bLogL. The biometric data obtained from this study includes information on species, sample numbers (N), standard length range, total weight range, and the length-weight relationship constants (a and b) for each species. In this study, we estimated the length-weight relationship of 16 freshwater fish species from some rivers of Morang district, Eastern Nepal. A total of 1,600 fish specimens, representing 16 different species from 5 families were studied from September 2022 to February 2023. The fishes were captured from the river and preserved in 20% formalin for subsequent biometric measurements in the laboratory. Biometric measurements were taken as follows: for each fish, length measurements were listed as standard length or fork length (SL in cm) from mouth to where the caudal fin is lobate. Length measurements were taken with a regular ruler validated against a Vernier Calliper, with an accuracy of 0.1 cm. Weight measurements were obtained using an electronic digital balance with a precision of 0.01 g. While listing weight, a fish consistency was maintained concerning the degree of wetness of the body to ensure accuracy. Among the species listed in the Morang district, Puntius terio has the smallest range of standard length (2.7 cm - 7.4 cm) and total weight (1.07 g - 7.06 g) while Garra gotyla gotyla has the largest range of standard length (4.3 cm - 18.6 cm) and total weight (4.5 g - 15.6 g). These variations indicate the natural size differences among the species. The analysis of the length-weight relationships revealed that all the studied fish species exhibited a negative allometric growth pattern. This means that as the length of the fish increases, its weight increases at a slower rate. The findings of this study contribute to our understanding of the growth patterns of freshwater fish species in the study area.